2021
DOI: 10.3390/en14238193
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Walking and Walkability in the Smart City through a Model Composite w2 Smart City Utility Index

Abstract: This paper explores walking and walkability in the smart city and makes a case for their centrality in the debate on the resilience and sustainability of smart cities, as outlined in the United Nations’ (UN) Sustainable Development Goals (SDGs). It is argued that, while the human/inhabitant-centric paradigm of urban development consolidates, and research on walking, walkability, and pedestrian satisfaction flourishes, the inroads of ICT render it necessary to reflect on these issues in the conceptually- and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…It addresses the exchange of information between management platforms and passengers, both in terms of informing and interacting with users and in terms of collecting direct, voluntary, or involuntary information to apply in the management and planning of urban mobility. Within this group, we nd studies that deal with delivering mobility information to passengers [33][34][35][36][37], studies on the accessibility of speci c groups such as the elderly [38-44], children [45], people with special needs [46][47][48], studies related to travel decision-making [49-51], tools to encourage passengers to use more sustainable modes of transportation [52-65], systems to stimulate passenger awareness with gami cation-focused apps [66-71], apps to encourage walking [72][73][74][75] and user behavior change towards more sustainable modes of mobility [76][77][78][79][80][81]. Additionally, the group also includes studies related to behavioral analysis based on social networks [82-84], creation of density maps using cell phone data [85,86], studies on population participation in mobility management decisions [87-89], and the development of crowdsourcing and crowdsensing practices [90][91][92][93][94][95][96][97][98][99][100].…”
Section: Subgroups Of It Studies Applied In Sustainable Urban Mobilitymentioning
confidence: 99%
“…It addresses the exchange of information between management platforms and passengers, both in terms of informing and interacting with users and in terms of collecting direct, voluntary, or involuntary information to apply in the management and planning of urban mobility. Within this group, we nd studies that deal with delivering mobility information to passengers [33][34][35][36][37], studies on the accessibility of speci c groups such as the elderly [38-44], children [45], people with special needs [46][47][48], studies related to travel decision-making [49-51], tools to encourage passengers to use more sustainable modes of transportation [52-65], systems to stimulate passenger awareness with gami cation-focused apps [66-71], apps to encourage walking [72][73][74][75] and user behavior change towards more sustainable modes of mobility [76][77][78][79][80][81]. Additionally, the group also includes studies related to behavioral analysis based on social networks [82-84], creation of density maps using cell phone data [85,86], studies on population participation in mobility management decisions [87-89], and the development of crowdsourcing and crowdsensing practices [90][91][92][93][94][95][96][97][98][99][100].…”
Section: Subgroups Of It Studies Applied In Sustainable Urban Mobilitymentioning
confidence: 99%
“…Cities all over the world seem to want to become more intelligent, outfitted with numerous innovative technologies (e.g., detectors, sensors, remote sensing, satellite imaging, machine learning, etc.) to become more dynamic and flexible in terms of addressing the challenges that regularly arise due to overcrowding, crowding, disasters, pandemics, and lack of comfort all contributing and leading to a decrease in overall well-being [65]. When AI is integrated with AI explainability, challenges such as power savings, traffic control, and industrial automation are themes where intelligence affects smart solutions, leading to faster and more intelligent decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another point of importance is the provision of a physical activity place,( not rigorous exercise), evidence-based research has shown that patients with accessibility to places for walking (Morris & Hardman, 1997;Ouf et al, 2021;Visvizi et al, 2021), meditation (Goyal et al, 2014;Innes et al, 2012;Scott, 2022), yoga (Maddux et al, 2018;Shohani et al, 2018;Woodyard, 2011), and mindfulness (Bartlett et al, 2021;Mohammed et al, 2018) are prone to lower stress levels, lower pain levels and overall general improvement, than ones not partaking in these types of activities. This entails that designers design easily accessible areas that fit these types of activities, both inside and outside to accommodate for weather changes.…”
Section: Physical Attributesmentioning
confidence: 99%